EXTENSÃO UNIVERSITÁRIA E INCLUSÃO SOCIAL: A EXPERIÊNCIA DO PROJETO CIDADANIA PARA TODOS - Souza, Mariana M. d.; Hauser, Ester E.; Ramos, Lizelia T.; Bedin, Juliana; Frue, Janaína; Menegon, Carolina (Salão do Conhecimento, 2013)
Resumo